Determination of heavy metal ions in aqueous solutions by phthalocyanine coated quartz crystal microbalance - Coban, C.; Demirbas, E. (Amer Scientific Publishers, 2006)
In this study, thin films of phthalocyanines coated on a quartz crystal microbalance were used to investigate amount of heavy metal ions (Pb2+ and Zn2+) present in aqueous solutions. The coated materials on quartz crystal microbalance were exposed to various concentrations of Pb2+ (129510360 ppm) and Zn2+ (409-3274 ppm) ions in aqueous solutions, respectively. Determination was based on the shifts in resonance frequency of a quartz crystal microbalance responds to small changes in mass due to the adsorption of heavy metal ions on its coated surface. The adsorption mechanism in between phthalocyanine films and heavy metal ions were analysed with using two adsorption isotherm models including two-step adsorption model and Henry's Law based on the experimental data in which two-step adsorption model is for non-linear response curves and the other is for linear response curves, respectively. The effect of changes in viscosity and density of aqueous heavy metal ion solutions on changes in the resonance frequency of the quartz crystal microbalance was explored. The free adsorption energies were also calculated which indicated that the adsorption process was spontaneous.
Keywords: quartz crystal microbalance; phthalocyanines; heavy metal ions; adsorption